Pressure-induced phase transitions and bandgap-tuning effect of methylammonium lead iodide perovskite - Jiang, Shaojie (2020)
Pressure-induced crystallographic transitions and optical behavior of MAPbI3 (MA=methylammonium) were investigated using in-situ synchrotron X-ray diffraction and laser-excited photoluminescence spectroscopy. We observed that the tetragonal phase that presents under ambient pressure transformed to a ReO3-type cubic phase at 0.3 GPa, which further converted into a putative orthorhombic structure at 2.7 GPa. The sample was finally separated into crystalline and amorphous fractions beyond 4.7 GPa. During the decompression, the phase-mixed material restored the original structure in two distinct pathways depending on the peak pressures. Being monitored using a laser-excited photoluminescence technique under each applied pressure, it was determined that the bandgap reduced with an increase of the pressure till 0.3 GPa and then enlarged with an increase of the pressure up to 2.7 GPa. This work lays the foundation for understanding pressure-induced phase transitions and bandgap tuning of MAPbI3, enriching potentially the toolkit for engineering perovskites related photovoltaic devices.